Lessons learned about empathy during our interview seasons. (2nd August 2020) - Kusz, Halina; Kakarala, Radhika; Champine, Andrew
Abstract: Empathy is one of the most valuable skills sought by patients from their physicians as well as by educators from their trainees. However, in medical education there is a general concern that, if not cultivated among students and residents, empathy may decline. We have assessed empathy self-perception among potential candidates who were applying to our internal medicine residency program. Interestingly, we observed that they have a good understanding and great appreciation of empathy values. Our candidates expressed that as medical students they were sympathetic and with experience, they are becoming more empathetic. They also depicted the different ways in which they learned about empathy. The lessons we learned from them lead us to conclude that the development of empathy is a multifaceted and a lifelong process, which must be cultivated during training years through many different modalities. We suggest that the patient's story, coaching skills and self-reflection, might be the most powerful ways of learning empathy.